A Review of Studies on Cooperative Learning in Language Classroom seen from Students' attitudes - Ika Harianingsih; Zailani Jusoh (ITScience (Information Technology and Science), 2022)
Cooperative learning is one of the most effective learning methods that has been widely used in higher education. In the language classroom, it can develop transferable skills and encourage students to use the language. The effectiveness has been argued in numerous of literature. However, not many are concerned about how students feel about being involved in a group learning process. Therefore, this article reviews the literature on cooperative learning in the English language classroom. The study aimed to seek the students' views regarding their experiences on group work both in online and offline settings. Based on the findings, the majority of the students who experienced group work online and offline have a positive perception. Utilizing a cooperative learning strategy may benefit students in various ways, including increased self-confidence and motivation, a more student-centered environment, and taking responsibility. In addition, online group work is considered a flexible learning strategy (i.e., time and place schedule management) and easy access to various teaching materials in online settings. Regardless of the benefits, the students who perceived group work negatively were in online settings due to internet connection issues, less group work experience, and unfamiliar with the application and software. Therefore, this study benefits students, academicians, and policymakers.